SENI MUZIK DI RAJA, NOBAT KEDAH DARUL AMAN - NURUL SYAFIQAH, BINTI NOOR AZMAN (Universiti Malaysia Sarawak(UNIMAS), 2019)
This research is about Royal Music, Nobat Kedah Darul Aman. The objective of this study is to identify management of nobat music art by the Sultan of Kedah Office in Kedah Darul Aman. Focusing on the methods and techniques of the nobat music art and musical instruments played during royal ceremonies. Additionally, this research examines the taboo in nobat music art. The data collection was done using the field work study method. The new discovery in this research is to introduce the special features of sounds and tools used in the Kedah nobat music art which is Malaysia’s oldest musical instrument in Malaysia.